Low-Cycle Fatigue Behavior of Nuclear-Grade Austenitic Stainless Steel Fabricated by Additive Manufacturing - Jianhui Shi; Huiqiang Liu; Zhengping Liu; Runzhong Wang; Huanchun Wu; Haitao Dong; Xinming Meng; Min Yu (Crystals)
The application of additive manufacturing technology in the field of nuclear power is becoming increasingly promising. The low-cycle fatigue behavior of Z2CN19-10 controlled-nitrogen-content stainless steel (SS) was investigated by fatigue equipment, scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), and transmission electron microscopy (TEM), including additive manufactured (AM) and forged materials. The results showed that the microstructure of the AM material exhibited anisotropy for the X, Y, and Z directions. The tensile and impact properties of the X, Y, and Z directions in AM material were similar. The fatigue life (Nf) of X- and Y-direction specimens was better than that of Z-direction specimens. The tensile, impact, and fatigue properties of all AM materials were lower than those of the forged specimens. The Z direction specimens of AM material showed the best plastic strain by the highest transition fatigue life (NT) during the fatigue strain amplitude at 0.3% to 0.6%. The forged specimens showed the best fatigue properties under the plastic strain amplitude control mode. Fatigue fracture surfaces of AM and forged materials exhibited multi- and single-fatigue crack initiation sites, respectively. This could be attributed to the presence of incompletely melted particles and manufacturing defects inside the AM specimens. The dislocation morphology of AM and forged fatigue specimens was observed to study the low-cycle fatigue behaviors in depth.